The Prophetic Dimension of KH. Ahmad Dahlan’s and KH.Hasyim Asy’ari’s Thought and its Implication in Education - Albany, Sulistiono Shalladdin (Al-Misbah (Jurnal Islamic Studies), 2021)
Prophetic dimension owned by KH. Ahmad Dahlan and KH. Hasyim Asy’ari is a privilege that they had. Muhammadiyah and NU education that realizes the thoughts of its founding fathers should have synergy in terms of the prophetic dimensions owned by the founding fathers. Research on Muhammadiyah Education and Muhammadiyah Teaching and NU Education and NU Teaching by studying the thoughts of KH. Ahmad Dahlan and KH. Hasyim Asy’ari through a prophetic analysis is necessary because it could be a material for the evaluation and development of Islamic Education in Indonesia to give more benefits for umat (society). The aims of research are to know the prophetic dimensions of KH. Ahmad Dahlan and KH. Hasyim Asy'ari about the concept of education and its implications in education. The results showed that KH owns the prophetic dimension in the humane education, element of liberation, element of transcendence, and direction in prayers. The Prophetic Dimension of KH. Hasyim Asy’ari is in the element of humane education, element of liberation, resistance to colonizers, element of transcendence, pure intention for knowledge seekers. The implications of the prophetic dimensions owned by KH. Ahmad Dahlan and KH. Hasyim Asy’ari on Muhammadiyah dan NU education for the development of Islamic Education in Indonesia are found on the aspect of system development of which the realization is the development of policy regarding the content of Islamic Education Curriculum at Schools.